2021
DOI: 10.3390/microorganisms9050947
|View full text |Cite
|
Sign up to set email alerts
|

Re-Emergence of Salmonellosis in Hog Farms: Outbreak and Bacteriological Characterization

Abstract: Clinical salmonellosis has been increasing significantly in Brazil in recent years. A total of 130 outbreaks distributed among 10 swine-producing states were investigated. One representative Salmonella isolate from each outbreak was characterized through serotyping, antimicrobial resistance profiles, PFGE, and WGS. From 130 outbreaks: 50 were enteric, 48 were septicemic, 17 cases were characterized as hepato-biliary invasive, 13 as nodal and two were not classified. The most prevalent serovars were a monophasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 67 publications
1
11
0
2
Order By: Relevance
“…S3). The pKPC-CAV1321 had been previously found in Citrobacter freundii and Klebsiella pneumoniae (Sheppard et al, 2016), and it was recently identified in Salmonella Choleraesuis spread in different Brazilian regions (Meneguzzi et al, 2021). However, so far, pKPC-CAV1321 has never been reported in any ExPEC lineage.…”
Section: Resultsmentioning
confidence: 99%
“…S3). The pKPC-CAV1321 had been previously found in Citrobacter freundii and Klebsiella pneumoniae (Sheppard et al, 2016), and it was recently identified in Salmonella Choleraesuis spread in different Brazilian regions (Meneguzzi et al, 2021). However, so far, pKPC-CAV1321 has never been reported in any ExPEC lineage.…”
Section: Resultsmentioning
confidence: 99%
“…This can ensure the proper administration of efficient antibiotic therapy when necessary and establish an epidemiological correlation among strains isolated from different sources. Although S. 1,4, [5],12:i:-is one of the most prevalent serotypes in Brazil, few studies have described the antimicrobial resistance profiles and genotypic diversity of the strains of this pathogen in Brazil [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Although S . 1,4, [5],12:i:- is one of the most prevalent serotypes in Brazil, few studies have described the antimicrobial resistance profiles and genotypic diversity of the strains of this pathogen in Brazil [24–29].…”
Section: Introductionmentioning
confidence: 99%
“…7 S. enterica is most frequently associated with clinical disease in domestic animals, with > 2,600 serovars identified. 7,8 In pigs, 2 main serovars of S. enterica are linked to clinical disease: Salmonella Choleraesuis, typically causing septicemic clinical disease; Salmonella Typhimurium, generally causing enteric clinical disease. 7 Infection occurs mainly through fecal-oral transmission, and most Salmonella infections are subclinical.…”
mentioning
confidence: 99%
“…8 Preweaning salmonellosis may be linked to environmental contamination, inadequate cleaning and disinfection of facilities, management mistakes, introduction of carrier animals, and poor infrastructure. 1,7,8 Furthermore, implementing effective measures to control and prevent salmonellosis can be challenging. These measures include biosecurity practices, adequate cleaning and disinfection, adopting all-in, all-out management, administration of antimicrobials in clinical cases, and the use of vaccines.…”
mentioning
confidence: 99%